Efficacy and tolerability of Avoine Rhealba containing cream in treatment of children with atopic dermatitis - Czarnecka-Operacz, Magdalena; Silny, Wojciech (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2003)
We investigated a group of 30 children with mild or moderate atopic dermatitis aged from 4 to 12 years. Avoine Rhealba containing cream was applied twice daily for the time period of 28 days and SCORAD index was used for evaluation of clinical severity of disease before treatment and after 14 and 28 days of therapy. Avoine Rhealba containing cream appeared to be an effective antiinflammatory agent causing significant reduction of SCORAD calculations in the course of treatment (p<0.001 after 14 and 28 days of therapy). No significant adverse events were reported and enhancement of the quality of life and reduction of insomnia were observed by parents of children participating in the trial. Also cosmetic qualities of the product (ease of application, consistency etc.) were highly appreciated by both patients and their parents.